Unraveling antibiotic resistance in Achromobacter mucicolens IA strain: genomic insights, structural analysis, and prospects for targeted therapeutics - Sura Ali Al-Asadi; Batool Hazim Abdul Wahhab; Jamila Bootwala; Wifaq M. Ali Alwatar; Rusul Emaduldeen S. Al-Kahachi (Microbiology Spectrum)
ABSTRACT The mortality rate of infectious diseases caused by Achromobacter mucicolens is increasing. The enhanced antibiotic resistance among bacterial species through genetic transfer and mutations in the efflux mediating genes has made the treatment quite challenging. A. mucicolens is an aerobic, gram-negative, and non-fermenting opportunistic pathogen found in immunocompromised patients. A. mucicolens shows resistance against beta-lactams and other antibiotics through intrinsic resistance mechanisms, including multi-drug efflux pumps and beta-lactamases. In this study, the clinical isolate whole genome sequencing of A. mucicolens data was analyzed to identify the genes and mutations responsible for antimicrobial resistance. The identified genes and their mutants were then subjected to structural analysis to better understand the impact of mutations on the protein structure, and domain analysis was performed to investigate the role of domains in antibiotic resistance. A total of 4 genes, acrR, macB, msbA, and tolC, were identified with significant mutations, whereas macB was shortlisted for further analysis based on the conserved regions, sequence alignment, and the maximum number of mutations. All the mutants of the macB gene contain the two common domains, the ABC transporter-like ATP-binding domain and the AAA + ATPase domain. These domains are crucial in efflux mediating drug transport and can be targeted to design novel drugs for treating infections caused by A. mucicolens.IMPORTANCEAchromobacter species represent a significant threat as opportunistic pathogens, particularly in healthcare settings. Their resilience to antibiotics, demonstrated by strains like A. mucicolens, poses a serious challenge in treating infections, especially in immunocompromised patients. This study emphasizes the critical need for heightened vigilance among healthcare professionals regarding Achromobacter infections. By analyzing the whole genome sequencing data of A. mucicolens, the study sheds light on the genetic basis of antimicrobial resistance, aiding in more targeted treatment strategies. Furthermore, structural and domain analyses offer insights into how mutations impact protein structure and function, crucial for developing effective interventions. Ultimately, implementing rigorous sanitation measures and antibiotic stewardship protocols is needed to mitigate the spread of Achromobacter and safeguard vulnerable patient populations.